Programa Nacional de Melhoria do Acesso e da Qualidade da Atenção Básica (PMAQ-AB) : a percepção dos trabalhadores quanto ao processo de implantação - Vieira, Elza Cléa Lopes (2016)
In this study, Access and Quality of Primary Care Improvement Program implementation process in a county in the state of Espírito Santo was evaluated. This is a descriptive study, exploratory, with qualitative approach that proposes as one of the central elements of production, the dialogue with the actors involved in the ongoing policy. Data collection was conducted through individual interviews using semi-structured script with doctors and nurses working in the health teams and family participating in the program under study. The interviews were transcribed and analyzed through thematic content analysis. The results indicated failures in the implementation process, such as involuntary membership in teams, inoperability of professional qualification actions and incipient management support. It was observed that an evaluative character that is linked to punishment and to the achievement of goals. On the other hand, the program produced positive effects in the work processes of the teams.